Nutritional composition, antioxidant properties of hylocereus polyrhizus powder and their effects on plasma glucose level and lipid profiles in diabetic rats and pre-diabetic subjects - Akhiruddin, Mohd Al-Saufreen (2013)
This study was carried out to determine nutritional composition, antioxidant properties of red pitaya (Hylocereus polyrhizus) powder (RPP) and to evaluate the effects of RPP consumption on blood glucose level and lipid profiles in streptozotocin-induced diabetic rats and pre-diabetic human subjects. The study consisted of three phases. In phase one, the proximate analyses of RPP were determined according to the methods of Association of Official Analytical Chemists (AOAC) international. Meanwhile, ascorbic acid assessment was carried out according to the modified method using high performance liquid chromatography (HPLC) assay. The RPP antioxidant power was determined using FRAP assay. The proximate composition of RPP were moisture (5.27 %), ash (1.22 g), carbohydrate (26.6 g), protein (1.59 g), fat (0.014 g), soluble fiber (12.05g) and insoluble fiber (5.65 g). The vitamin C content was 32.14 mg/100 g. The FRAP assay value of RPP was 31.36 ± 3.45 μM/100g or 8.72 ± 0.16 mg/100g. In phase two, study on hypoglycemic effects of RPP on plasma glucose level and lipid profiles in diabetic induced rats was conducted. This study used forty eight male Sprague-Dawley rats weight between 250 g-300 g. All the rats were divided equally into six groups. The groups consisted of control groups (NC & DC) and treatment groups (NPP, DPP, DPPM & DM). After four weeks of treatment, all treatment groups had showed significantly reduced (p<0.05) in the plasma glucose level. The highest percentage reduction in glucose level was observed in DPPM group with 69.97 %. For plasma total cholesterol (TC) level, the highest percentage reduction was observed in NPP group with 62.39 %. In phase three, community trials were conducted among pre-diabetic human subjects at Felda Mempaga Bentong, Pahang. Total thirty six subjects were randomly divided into two groups which were pre-diabetic treatment groups consisted of PT3 (consumed 60 g RPP/day), PT4 (consumed 80 g RPP/day), and PT5 (consumed 100 g RPP/day) and pre-diabetic control groups which were not consumed RPP. For plasma glucose level, among treatment groups, PT5 had showed the highest percentage of reduction (22.90 %) with significant difference (p<0.05) in the mean plasma blood glucose level after 4 weeks of treatment. For plasma lipid profiles, showed that group PT5 had the highest percentage of reduction with significant difference (p<0.05) in TC (26.44 %), TG (20.54 %), and LDL-C (49.55%) levels followed by PT4 and PT3 groups after 4 weeks of treatment. For HDL-C level, PT5 group also showed the highest percentage of increment 63.8 %. The results revealed that all dosages of RPP drinks showed positive effects in increasing HDL-C and TAS levels, in the same time lowering glucose, TC, TG and LDL-C levels in pre-diabetic subjects.